Hypokalemia in Exertional Heat Illness with Emphasis on Extreme Exercise and Military Practice - Fransiska Pratiwi, Ardita (Syntax Literate, 2026)
This study addresses the growing concern of exertional heat illness (EHI) in extreme exercise and military training environments, where physiological stress is intensified by heat exposure, dehydration, and high physical demands. One critical but often underemphasized factor in EHI is hypokalemia, an electrolyte imbalance that can impair cardiac function, neuromuscular performance, and renal regulation. Therefore, this research aims to analyze the role of hypokalemia in the development and progression of EHI, particularly under conditions of prolonged and high-intensity physical activity. This study employs a qualitative approach using a narrative literature review design. Data were collected from reputable scientific databases, including PubMed, ScienceDirect, and Web of Science, focusing on peer-reviewed articles related to hypokalemia, heat stress, and exercise physiology. A purposive sampling technique was used to select relevant studies, and the data were analyzed using thematic synthesis to identify patterns and relationships. The findings indicate that hypokalemia frequently occurs in individuals experiencing EHI due to factors such as excessive sweating, dehydration, hormonal regulation, and renal potassium loss. These disturbances contribute to impaired cardiovascular stability, reduced muscle performance, and increased risk of complications such as arrhythmias and kidney injury. In conclusion, hypokalemia plays a significant role in exacerbating the physiological burden of EHI. Integrating electrolyte monitoring and management into training and recovery protocols is essential to reduce health risks and improve performance outcomes in extreme environments.